Технологія борошняних виробів грузинської кухні з використанням аглютенового борошна - Антоненко, Артем Васильович; Василенко, Олена Вікторівна; Земліна, Юлія Володимирівна; Бровенко, Тетяна Вікторівна; Стукальська (Іванова), Наталія Миколаївна; Толок, Галина Арсенівна (My University, 2021)
У статті висвітлено актуальність розроблення борошняних виробів грузинської кухні з використанням аглютенового борошна. Обґрунтовано технологію безглютенового хачапурі з сиром з використанням аглютенових видів борошна – кукурудзяного, рисового та структуроутворювачів – крохмалю кукурудзяного і комплексу полісахаридів льону. Розроблені вироби характеризуються високими показниками якості та конкурентопридатності, їх можна пропонувати для оздоровчого харчування різних верств населення, та харчування хворих на глютенову ентеропатію. Завдяки високому вмісту харчових волокон, зокрема цінних для профілактики серцево-судинних захворювань, ожиріння та раку кишківника розчинних волокон борошна льону, його можна рекомендувати для оздоровчого раціону людей, які працюють на токсичних виробництвах та проживають на екологічно забруднених територіях. The article highlights the relevance of the development of flour products of Georgian cuisine using gluten-free flour. The technology of gluten – free khachapuri with cheese with the use of gluten – free types of flour – corn, rice and structurants – corn starch and a complex of polysaccharides of flax is substantiated. Traditional khachapuri technology involves the use of wheat flour, which cannot be used in the production of gluten products due to the presence of gluten in gluten proteins. However, according to previous research, other types of gluten-free flour can be effectively used in the production of gluten-free products – corn, rice in combination with effective structuring agents – starch, non-starch polysaccharides. In this regard, we proposed in the production of yeast dough for khachapuri to use a flour mixture of corn and rice flour in combination with corn starch and flaxseed flour, which is characterized by a complex of polysaccharides – cellulose, insoluble polymers of phenolic slime, lime. The share of dietary fiber is up to 28 % by weight of flax seeds or nonfat flaxseed flour. Dietary fiber helps to stimulate the intestines in constipation, play a positive role in reducing the risk of coronary heart disease, preventing bowel cancer, reducing obesity. Flaxseed mucus has a well-defined ability to swell, and therefore show high viscosity in aqueous solution or suspension. The hydrocolloid nature of the mucus has a beneficial effect on the water-binding and emulsifying properties of flaxseed flour. The developed products are characterized by high quality and competitiveness, they can be offered for health nutrition of various segments of the population, and nutrition of patients with gluten enteropathy. Due to the high content of dietary fiber, in particular valuable for the prevention of cardiovascular disease, obesity and colon cancer soluble fiber flax flour, it can be recommended for the health of people I work in toxic industries and live in environmentally polluted areas.
Keywords: кафедра технології ресторанної і аюрведичної продукції; технологія; борошняний виріб; хачапурі; модельні композиції; хімічний склад; technology; flour product; khachapuri; model compositions; chemical composition